Nasal and Nasopharyngeal Rosai-Dorfman Disease - Kelly Di Dier; Marc Lemmerling; Geert De Vos (Journal of the Belgian Society of Radiology, 2022)
Teaching Point: Nasal and nasopharyngeal Rosai-Dorfman disease is a rare cause of nasal obstruction.